Implementasi pembayaran SPP menggunakan sistem pembayaran digital berbasis syariah di Pondok Pesantren Ar-Rahmah - Nurhasanah Nurhasanah; Nurse Fatimah Mz; Rian Handika (STAI Auliaurrasyidin Tembilahan, 2026)
This study aims to examine the implementation of digital tuition payments and the obstacles that arise in the process. This research is a field study with a descriptive qualitative model, with the main instruments for data collection being observation, in-depth interviews, and documentation. The results indicate that the implementation of the digital payment system at the Ar-Rahmah Islamic Boarding School can be categorized as successful and effective. This system is able to meet the needs of the Islamic boarding school in terms of efficiency and accountability, while also making it easier for guardians to fulfill financial obligations. Although the implementation of the Sharia-based digital payment system at the Ar-Rahmah Islamic Boarding School is considered to have brought many benefits, this study identified a number of obstacles that are still consistently faced by both guardians and the administration. Broadly speaking, these obstacles can be grouped into six main categories: digital literacy, lack of information, network constraints, system disruptions, manual verification, and human error.